Carlos García (ed.), Discreta efusión. Jorge Luis Borges y Alfonso Reyes. Epistolario (1923-1959) y crónica de una amistad. Bonilla Artigas-El Colegio de México, México, 2010. - Cajero Vázquez, Antonio (El Colegio de México, 2013)
Se reseña el libro:Discreta efusión. Jorge Luis Borges y Alfonso Reyes. Epistolario (1923-1959) y crónica de una amistad.